Optimization and control of the work program in the financial management subsystem of the construction organization - Voitovych, V.A.; Chupryna, Iu. A. (Ways to Improve Construction Efficiency, 2023)
In the dynamic world of construction, financial management plays a key role in the success and sustainability of the company. Effective financial management ensures that a construction company can complete projects on time, maintain profitability and withstand economic fluctuations. Effective budgeting and cost control ensure projects stay on schedule, reducing the risk of cost overruns and delays. It also enables better decision-making because project managers can identify areas where savings can be implemented without compromising quality. Management of work programs of a construction enterprise from the point of view of financial management should include a balance between detailed regulation of their branch functions in order to increase productivity and improve the quality of construction works and materials and price. This will contribute to the achievement of socio-economic and technical tasks in the general development of Ukraine. To ensure the sustainable development of the construction organization, it is necessary to reorient the existing systems and determine the priority areas of management. The role of construction organizations in achieving strategic social goals depends on the implementation of investment plans and the final results achieved through their implementation. At the same time, it is important to increase the productivity of the construction complex by rationally using investment resources and directing them to projects that provide maximum economic and social impact, as well as high profitability of completed projects. In Ukraine, the development of investment and construction complexes takes place in conditions of fierce competition and low investment activity. In the context of post-war recovery, market demands for technical and economic aspects of construction are growing. Construction objects require various optimization approaches and financial control, which makes the issue of financial management of construction organizations quite relevant, as those investments that are available must be able to be used correctly. This article examines the main components of financial management in the construction industry with an emphasis on budget optimization and its financial control.